WATER QUALITY MODELS: A REVIEW - Sumita, Nair; Kaur, Bhatia Sukhpreet (International Journal of Research -GRANTHAALAYAH, 2017)
Maintaining water quality and predicting the fate of water pollutants are one of the important tasks of present environmental problems. The best tool for predicting different pollution scenarios are the simulation of mathematical models which can provide a basis and technical support for environmental management.